Assessing full body impulsive ability using a range of medicine ball loads for the backward overhead medicine ball throw - Beckham, G, K.; Martin, E.; Layne, D, K.; Luke, R.; Mayhew, J. L. (Sports Biomechanics, 2023)
The potential for high performance in many sports can be assessed by quantifying whole-body explosiveness. The backwards overhead medicine ball (BOMB) throw is commonly-used to tests this ability, but the effect of varied loading on test execution is unknown. The purpose of this study was to determine the effect of different medicine ball (MB) loads on force, velocity, and power output during the BOMB throw. Female collegiate softball and rugby players (n=31) performed the BOMB throw on a force plate using 2.7, 3.6, 4.5, and 5.5 kg MBs, with three throws per load in a randomised order, and 30 seconds rest between throws. A series of Repeated Measures ANOVAs noted no differences (p>0.05) in peak power, peak force, peak velocity, force at the moment of peak power, or velocity at the moment of peak power, across MB loads. The lack of differences among these loads indicates that coaches can likely compare kinetic characteristics of the BOMB throw within this range (2.7-5.5 kg). Therefore, coaches can use the BOMB throw with 2.7-5.5 kg MBs for training or measurement among female athletes to obtain reference data for programming or evaluation.